Peer Group Method Can Improve Adolescent Behavior in Prevention of Cervical Cancer - Dina Isfentiani; Kasiati Kasiati; Sunarto Sunarto (Community Empowerment in Health, 2023)
Cervical cancer is a disease that often attacks women's reproductive health. So we need a communityempowerment in the form of training of trainers to improve cervical cancer prevention behavior inadolescents with a peer group method approach. Facilitation activities include counseling on peer group learning methods, conducting training on improving behavior in preventing cervical cancer with the peer group method for adolescents. Activities carried out for one month, starting from planning, preparation, implementation and evaluation. This training was able to increase knowledge, attitudes and behavior in preventing cervical cancer in adolescents. It is recommended that participants who have been trained to be tutors are able to train their peers at school and in their neighborhood.